Chemoprevention of elite tea variety CFT‐1 rich in EGCG against chemically induced liver cancer in rats. Issue 8 (4th July 2019) - Liao, Sufeng; Lin, Jinke; Liu, Jianghong; Chen, Tuansheng; Xu, Ming; Zheng, Jingui
Abstract: Camellia sinensis (L.) O. Kuntze cv. CFT‐1 is an elite tea variety bred by sexual hybridization with a high content of epigallocatechin‐3‐gallate (EGCG) as 134.2 mg/g (which is 2.54‐fold that of the common variety). This study was to evaluate the chemopreventive effects of CFT‐1 green tea infusion (CFT‐1) against N ‐nitrosodiethylamine (NDEA)‐induced hepatocarcinogenesis in rats and its mechanisms. The results showed that CFT‐1 had a superior inhibitory effect in NDEA‐initiated hepatocarcinogenesis compared to that of common tea. CFT‐1 significantly reduced the hepatic nodules incidence, size, and number and prevented the hepatic adenoma or hepatocellular carcinoma (HCC) formation. In particular, CFT‐1‐treated animals had the least incidence of HCC (8.33%) followed by common tea treatment (40.00%) and model control rats (87.50%). CFT‐1 treatment significantly ameliorated abnormal liver function enzymes, reduced serum AFP, CEA, TSGF, and TNF‐α levels, inhibited the dickkopf‐related protein‐1 expression, enhanced antioxidant capacity, suppressed the production of livers 8‐hydroxy‐2′‐deoxyguanosine, and regulated hepatic phase I and II xenobiotic‐metabolizing enzymes. Transcriptomic analysis of liver tissue suggested that compared to common tea, administration of CFT‐1 regulated larger gene sets, which were located in several important pathways of antioxidants, inflammatory network, xenobiotic‐metabolizing enzymes, apoptosis, cell proliferation, and metabolism associated with liver tumorigenesis. We identified some genes as potential molecular targets involved in the prevention of CFT‐1 and found that CFT‐1 inhibited inflammation response, proliferation, and accelerated apoptosis by inhibiting NF‐κB and PI3K/Akt pathway. Thus, EGCG‐rich CFT‐1 green tea might be a potential choice for liver cancer prevention/treatment in the future. Abstract : Camellia sinensis (L.) O. Kuntze cv. CFT‐1 is an elite tea variety bred by sexual hybridization with a high epigallocatechin‐3‐gallate (EGCG) content of as 134.2 mg/g (which is 2.54‐fold that of the common variety) in our previous study. In this study, CFT‐1 green tea infusion significantly reduced the hepatic nodules incidence, size, and number and prevented the hepatic adenoma or hepatocellular carcinoma (HCC) formation induced by N ‐nitrosodiethylamine (NDEA). In particular, CFT‐1‐treated animals had the least incidence of HCC (8.33%) followed by common tea treatment (40.00%) and model control rats (87.50%).